Pathêt: di Atas Kertas dan di Atas Panggung Wayang Kulit dalam Perspektif Teori Praktik - Wisma Nugraha Christianto; Timbul Haryono; G. R. Lono L. Simatupang; Soetarno - (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
Pathêt: on the Paper and on the Stage of Shadow Puppet Theater in Practice Theory Perspectif. Researchesabout karawitan focusing on pathêt has given conceptual result which repairs and clarifi es the result of previousresearches, with different paradigms. Some are even repetitive. On the other hand, in the practical level and socialdevelopment, some changes and dynamic art performing paradigm have changed. If the researches and the researchparadigms on this matter cannot accommodate the changes, the result will be static. There have been some pathêtresearches that inspired a critical development of karawitan and performance studies. The result of the researchesimplied a temporal context, demanding revisiting on the temporary context and its relation to non-theoretical matter,partial, practicality, and social reality. A scientifi c construction based on human activity as a practice is neededto construct scientifi c atmosphere to balance social dynamics, performance, and the harmony of gending karawitanrelated to the utilization of pathêt as a part of coherent structure. Social reality of wayang kulit stage is close to theaesthetic and art feel towards karawitan music. Social structure and performance structure in the present time do notalways posses linier relation to the symbolic structure and past aesthetic. Symbolic and aesthetic constructs have theability of symbolic formation and high level of musical appreciation. Therefore, Pierre Bourdieu’s practical critiqueserves as an alternative encouragement reacting to critical pretension towards problem solution and reception ofpathêt in the conceptual and practical level